ANALYSIS STUDY OF CLOVE LEAF (SYZYGIUM AROMATICUM) EXTRACT ABSORBANCE USING UV-VIS SPECTROPHOTOMETER: STUDI ANALISIS ABSORBANSI EKSTRAK DAUN CENGKEH (SYZYGIUM AROMATICUM) MENGGUNAKAN UV-VIS SPECTROPHOTOMETER - Natasya Frysilia Wardanni; Iwan Sugihartono; Anggara Budi Susila; Rahmat Setiawan Mohar (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
This study reports that clove (Syzygium aromaticum) leaf extract was used as a reducing agent and deionized water was used as a solvent. In the process of making the extract, as much as 20 grams of clove leaf powder was mixed with 100 mL of deionized water and boiled using a hotplate magnetic stirrer for 2 hours at a temperature of 70°C. Then, the extract solution was filtered using 11 cm diameter filter paper and centrifuged at 4000 rpm for 30 minutes to obtain clove leaf extract. The extract was characterized using UV-Vis Spectrophotometer to analyze the absorbance and energy band gap. Based on the absorbance test results, clove leaf extract showed maximum absorption at a concentration of 1000 ppm with a wavelength of 221 nm and at a concentration of 500 ppm with a wavelength of 225 nm. The energy band gap value at a concentration of 1000 ppm is 3.26 eV and at a concentration of 500 ppm 3.38 eV.